Tingkat Formulasi Model Soal dalam Permutasi Acak Menggunakan Algoritma Fisher Yates - Puji Chairu Sabila; Gunadi Widi Nurcahyo (Jurnal Sistim Informasi dan Teknologi, 2021)
The problem model in random permutations results in random randomization of the most commonly used questions in exam practice in education ranging from elementary school to college level and even some agencies that utilize exams to test one's abilities. This Problem Model can produce a high random percentage with more complex processes compared to analogues. Conduct Model Formulations on infinite questions so that they can be easily utilized without complicated calculations. The problems processed in this study are from 50 questions, and 12 students are sourced from the Information System Study Program of STMIK Logika, at Medan Indonesia state. Based on the collection of the question by the head of the study program in charge of the STMIK. Furthermore, the problem is saved into the database. The next stage is to randomize the question based on the number of students taking the exam. The problem has been randomized into a model formulation of the question in a random permutation of the question at the time of the Test practice. The result of the test on this question is a matter of courses. Randomized questions can form a problem model in random permutations based on many questions, the number of questions. All questions are made by lecturers who teach courses and help the study program in the teaching and learning process with the formulation of the problem model.